(untitled) (International conference on multidisciplinary science, 2024)
This article explores effective strategies for teaching in the digital age, with a focus on online education. It examines the benefits and challenges of digital learning environments and offers practical methods to enhance student engagement, ensure accessibility, and maintain academic rigor. The article highlights best practices for integrating technology, fostering interactive learning, and supporting diverse learners, aiming to help educators create effective and inclusive online educational experiences.